G372(P) A systematic review of breakthrough pain assessment tools and their psychometric properties. (25th October 2020) - Greenfield, K; Holley, S; Schoth, DE; Harrop, E; Bayliss, J; Anderson, A-K; Howard, RF; Liossi, C; Johnson, M; Rajapakse, D; Fraser, LK; Mott, C; et al.
Abstract : Background: Breakthrough pain is commonly experienced by both children and adults with cancer, and also by patients with other terminal conditions, including those approaching end-of-life. Management of breakthrough pain is often insufficient, which could be due in part to a current lack of validated assessment tools. The aims of this systematic review are to (1) identify all available instruments measuring breakthrough pain in infants, children, adolescents or adults, and (2) critically appraise, compare and summarise the quality of the measurement properties of each identified instrument using established COSMIN criteria. Methods: Two searches were carried out, one corresponding to each aim of the review. For both, the Cochrane Library, PROSPERO, EMBASE, CINAHL, MEDLINE, PsychINFO, Web of Science Core Collection, Google Scholar, the ProQuest Dissertations & Theses Database, Evidence Search and OpenGrey were searched from the inception of each database to October 2019. Search terms were derived from a thorough reading of relevant literature and in discussion with a medical librarian. Results: Seven breakthrough pain tools were identified, only one of these - The Breakthrough Pain Questionnaire for Children - was designed for use in children. This tool, however, has not been validated to date. A further 40 studies were identified that used bespoke breakthrough pain assessment tools. Conclusion: There is a lack of validated tools for assessing breakthrough pain, particularly in infants, children and young people. These are urgently needed so that the assessment and management of this distressing symptom can be further improved.